1 Answer | Add Yours
You need to transform the sum `sin 7x + sin 3x` and difference `cos 9x - cos x` into products such that:
`sin 7x + sin 3x =2 sin ((7x + 3x)/2)*cos ((7x - 3x)/2)`
`sin 7x + sin 3x =2 sin 5x*cos 2x`
`cos 9x - cos x = -2 sin ((9x + x)/2)*sin ((9x - x)/2)`
`cos 9x - cos x = -2 sin 5x* sin 4x`
The fraction `(sin7x+sin3x)/(cos9x-cosx) ` cancels only if `sin7x+sin3x = 0` , hence `2 sin 5x*cos 2x = 0 =gt sin 5x = 0` or `cos 2x = 0`
Notice that `sin 5x` is factor of product `-2 sin 5x* sin 4x` found to denominator. Since denominator needs to be different of 0, then `sin 5x != 0` , which contradicts `sin 5x= 0` .
Considering `sin 5x!=0` , then only `cos 2x = 0` may cancel the numerator.
You notice that `cos 2x` is also a factor of product to denominator since `sin 4x = 2 sin 2x* cos 2x` , hence `cos 2x!= 0` .
Since `sin 5x ` and `cos 2x` are both factors of products found to numerator and denominator, they need to be different of 0.
Since `sin 5x!=0` ; `cos 2x!=0` => `2 sin 5x*cos 2x != 0` , hence the fraction `(sin7x+sin3x)/(cos9x-cosx) != 0` and there are no solutions to equation `(sin7x+sin3x)/(cos9x-cosx) = ` 0.
We’ve answered 317,561 questions. We can answer yours, too.Ask a question